Artificial intelligence, technologies and the future of law schools - Mohammad, Mohammad Tahir Sabit; Ali Mohamed, Ashgar Ali; Omoola, Sodiq (The Malaysian Current Law Journal Sdn Bhd, 2019)
This paper looks at the use and utility of artificial intelligence (AI) in the area of legal profession globally and in Malaysia. The objective of the article was to highlight the types of AIs and their capabilities, and the effect of such technologies on the effectiveness and efficiency of legal service, as well as the threat that they may present to millions of graduates of law in the workplace. The research was conducted in the form of an integrated literature review by analysing and synthesising various ideas and opinions relating to the primary objective of the paper. It is found that the threat of technology is very minimal and it may affect those in lower ranks who see no need for upgrading their skills. Overall, it is found that AIs improve work efficiency and save costs, on top of fast and cheap delivery of legal services. The paper suggests that Malaysian legal services and education curriculum embrace the technology, and prepare their graduates in skills needed in high tech environments.